2011
DOI: 10.1530/joe-10-0436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous glucocorticoid secretion on the interleukin-6 response to bacterial endotoxin in pregnant and non-pregnant rats

Abstract: Glucocorticoids (GCs) are released in response to immune activation by the bacterial endotoxin, lipopolysaccharide (LPS). However, GC secretion in response to immune activation and other stressors is attenuated at term of pregnancy. GCs are important modulators of the immune response, and both pro-and anti-inflammatory effects are described. Here, we examined whether GC secretion in response to LPS is maintained in earlier pregnancy before term, and investigated the role of endogenous GCs in modulating LPS-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…55 However, other researchers have described an inhibition of LPSinduced TNF-a by MET. 56 With these last results in mind, some authors have suggested that an enzyme of the cytochrome P450 family might be involved in the signaling pathway leading to TNF-a production. This would be another effect of MET administration apart from the already described blockade of glucocorticoids (GC) synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…55 However, other researchers have described an inhibition of LPSinduced TNF-a by MET. 56 With these last results in mind, some authors have suggested that an enzyme of the cytochrome P450 family might be involved in the signaling pathway leading to TNF-a production. This would be another effect of MET administration apart from the already described blockade of glucocorticoids (GC) synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have been done in mice. While there is a somewhat smaller literature in rats there is a related literature on prenatal LPS in rats, e.g., (Romero et al, 2007;Harvey and Boksa, 2011;Nouel et al, 2011;Cui et al, 2009;Cui et al, 2011;Ashdown et al, 2006;Fortier et al, 2007;Fortier et al, 2004a) supporting the connection between prenatal immune activation and adverse effects on brain development in the progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Primena LPS-a i uzimanje krvi gravidnim ženkama Gravidnim ženkama pacova (n = 8 po tretmanu), telesne mase između 300 i 400 g, jednom dnevno je, intraperitonealnim putem, primenjivano 100 µg/kg lipopolisaharida (LPS), komponente ćelijskog zida Gram negativnih bakterija (serotip LPS-a iz bakterije Escherichia coli 0111:B4, Sigma, Nemačka) koji smo rastvorili u fiziološkom rastvoru (LPS grupa), ili 1 ml/kg sterilnog fiziološkog rastvora (SAL grupa), i to 15. i 16. dana gestacije [7] između 10 h i 12 h. Gravidnim ženkama je 15. dana gestacije dva sata nakon tretmana (LPS ili SAL) uzimana krv iz repne vene heparinizovanim "leptir" infuzionim sistemom, koja je potom preneta u heparinizovane ependorfice. Prikupljeni uzorci krvi su centrifugirani 10 minuta na 5000 g i temperaturi od 4°C.…”
Section: Materijal I Metode Eksperimentalne žIvotinjeunclassified